2010
DOI: 10.1111/j.1750-3841.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Antimicrobial Silver from Composites of Polylactide with Silver Zeolites

Abstract: Silver exchanged zeolites incorporated in food contact polymers are gaining importance as antimicrobial agents. Migration of silver ions from polymer matrices, however, is legally restricted. Therefore a compromise between silver migration and antimicrobial activity needs to be critically analyzed to validate novel materials in food packaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 21 publications
0
77
1
2
Order By: Relevance
“…Ag + ions are ion-exchanged out of the zeolite powder into media and are sufficient to cause bacterial cell death in both E coli and Staphylococcus aureus. 9,10 In the case of Ag + -zeolite, the release of Ag + into solution is primarily determined by the ionic strength of the medium, because this is an ion-exchange process and is media-dependent. Recently, there has also been a report of AgNP in zeolite powders and their activity towards Gram-positive and Gramnegative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Ag + ions are ion-exchanged out of the zeolite powder into media and are sufficient to cause bacterial cell death in both E coli and Staphylococcus aureus. 9,10 In the case of Ag + -zeolite, the release of Ag + into solution is primarily determined by the ionic strength of the medium, because this is an ion-exchange process and is media-dependent. Recently, there has also been a report of AgNP in zeolite powders and their activity towards Gram-positive and Gramnegative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Silver-containing zeolite compounds received approval of Food and Drug Administration (FDA) for being used as food contact surfaces (Joerger, 2007). Silver-zeolites have already been incorporated into polymeric films yielding antimicrobial properties (Kamisoglu et al, 2008;Zampino et al, 2008;Fernández et al, 2010). Polymer composites of plasticized poly(vinylchloride) pellets with silver zeolites demonstrated activity against S. epidermidis and E. coli (Zampino et al, 2008), while polyurethane composites with silver zeolites showed antimicrobial action against E. coli (Kamisoglu et al, 2008) and polylactid acidpolylactide (PLA)/silver zeolite composites also presented activity against S. aureus and E. coli, with silver being effectively released from the films .…”
Section: B Amentioning
confidence: 99%
“…Moreover, the European Food Safety Agency (EFSA) stated that in order to attain antibacterial effects, migrated ions ought to be in the range of the legal limit of 50 lg Ag ? /kg food (Fernandez et al 2010). Thus, our material could be safe for food packaging because its release is lower than legal limit.…”
Section: Morphology Analysis Of Nanofibersmentioning
confidence: 99%